2018
DOI: 10.5539/jas.v10n2p48
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Mustard Seed Meal for Weed Suppression in Potato (Solanum tuberosum)

Abstract: Mustard seed meal (MSM) derived from Sinapis alba controls weeds for several weeks following application to soil, but also has potential to injure the planted crop. Producers of certified organic potatoes typically utilize a combination of cover crops, soil hilling, harrowing, and cultivation for weed control. Once the potato canopy nears row closure, most late emerging weeds are suppressed by the dense potato canopy. MSM may have value for early season weed suppression in potato, but has not been previously t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 23 publications
(42 reference statements)
3
6
2
Order By: Relevance
“…There is almost no information on the response of pumpkin plants following the pre-emergence application of MSM and SSM, especially at different rates. However, these results were in agreement with previous studies for other crops such as potato plants, where MSM at 2.2 MT ha −1 showed a 2% injury on potato plants that were recovered later [26]. In contrast with other studies, MSM at 2.25 and 4.5 MT ha −1 severely reduced crop establishment of direct-seeded cucurbits [29], and lettuce emergence was reduced by at least 75% when planted into 3% (w/w) yellow mustard-amended soil earlier than 5 weeks after meal application [23].…”
Section: Crop Responsesupporting
confidence: 93%
See 3 more Smart Citations
“…There is almost no information on the response of pumpkin plants following the pre-emergence application of MSM and SSM, especially at different rates. However, these results were in agreement with previous studies for other crops such as potato plants, where MSM at 2.2 MT ha −1 showed a 2% injury on potato plants that were recovered later [26]. In contrast with other studies, MSM at 2.25 and 4.5 MT ha −1 severely reduced crop establishment of direct-seeded cucurbits [29], and lettuce emergence was reduced by at least 75% when planted into 3% (w/w) yellow mustard-amended soil earlier than 5 weeks after meal application [23].…”
Section: Crop Responsesupporting
confidence: 93%
“…While MM 2 provided 61% and 65% of narrow leaf and broadleaf weed control, respectively, as compared to the untreated control, MM 1 and both SSM treatments controlled weeds less than 60%. Our observations in direct-seeded pumpkin are in essential agreement with previous studies for various crops, where MSM at 2.2 to 4.5 MT ha −1 reduced early season weed density in cucurbits, onions, broccoli, and potato [26,29,36,57]. Darby et al [58] also reported similar results with sunflower and mustard seed meals in sweet corn.…”
Section: Weed Density and Biomasssupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, GSLs are found throughout Brassicaceae plant tissues but they are most concentrated in the seeds [30,31]. Evidence from previous studies have confirmed that BSMs can be used as a potential bioherbicide [25,[32][33][34]. Applying 3% Indian mustard seed meal in the soil reduced plant biomass of redroot pigweed by 74% as compared to unamended control [26].…”
Section: Introductionmentioning
confidence: 95%